Regional dynamics and mechanisms behind SARS-CoV-2 XDV.1 prevalence in Chongqing via genomic surveillance and molecular insights - Jin Yan; Fangyuan Liu; Sihan Hu; Junyi Pan; Qi Yan; Lu Yao; Huhao Jin; Xiaofeng Chen; Jiuhong He (Virus Research)
The evolution of SARS-CoV-2 has led to the emergence of numerous variants driven by genetic mutations and evolutionary pressures, posing significant challenges to public health. Understanding the molecular mechanisms and epidemiological advantages of variants like XDV.1 remains incomplete. This study analyzed SARS-CoV-2 samples collected in Chongqing from January to August 2024 through genomic surveillance and molecular dynamics simulations. Whole-genome sequencing identified dominant variants, and all-atom simulations assessed the effects of key mutations in the receptor-binding domain (RBD) on ACE2 receptor interactions, including changes in binding free energy. Genomic analysis identified XDV.1 as the dominant variant, characterized by RBD mutations L455S and F456L. These mutations disrupted conserved hydrophobic interactions and caused structural rearrangements. Simulations revealed that these changes increased binding free energy (ΔG = -4.57 kcal/mol) but reduced binding affinity compared to BA.2.86 and JN.1. XDV.1 exhibits structural features suggestive of potential immune evasion mechanisms, including conformational shifts and novel hydrogen-bond networks that could interfere with antibody recognition. These observed structural modifications, rather than increased receptor-binding affinity, may contribute to its widespread prevalence, though direct experimental validation of antibody interactions remains to be investigated. These findings offer valuable insights for vaccine development and epidemiological studies, highlighting the importance of interactions between structural and non-structural proteins in variant adaptation.